2018
DOI: 10.28991/cej-0309168
|View full text |Cite
|
Sign up to set email alerts
|

Public Evaluation of Speed Humps Performance and Effectiveness

Abstract: In Egypt, it is believed that speed humps are the cheapest and best solutions to reduce vehicles speed and thus reduce the number of potential accidents. Due to the lack of specifications in Egypt that govern the installation of speed humps, they were spread randomly and with different dimensions without adequate studies. Consequently, this practice can cause adverse effects on the road users and the surrounding environment. For this purpose, a questionnaire was designed to discuss the different effects of usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Consequently, the use of speed humps can cause a negative effect to emergency response times. If there no strict control on its installation process according to wellconsidered standards, other means should be considered for calming traffic in residential areas [2].…”
Section: E Impact Of Speed Humps' Characteristics On Vehicles'mentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, the use of speed humps can cause a negative effect to emergency response times. If there no strict control on its installation process according to wellconsidered standards, other means should be considered for calming traffic in residential areas [2].…”
Section: E Impact Of Speed Humps' Characteristics On Vehicles'mentioning
confidence: 99%
“…Traffic calming is defined by the Institute of Traffic Engineers (ITE) as "the combination of mainly physical measures to reduce the negative effects of motor vehicle use, alter driver behavior, and improve conditions for nonmotorized street users" [1,2]. Since speed humps are a very effective means of calming traffic, the main purpose of installation of speed humps is to reduce speed and volume of traffic to acceptable limits in order to enhance safety for pedestrians and motorists [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on data from Iraq U-turn sites, Al-Obaedi [15] reported that speed humps reduced the merging time by more than 50%. Shwaly et al [17], based on a questionnaire in Egypt, found that both vehicle speeds and accident rates significantly reduced as the effect of speed humps.…”
Section: Introductionmentioning
confidence: 99%